An Investigation into City Slogan and Its Communication Effect - Wang, Ziyi; Yi, Gege; Zhang, Yuting; Dong, Jingyao; Wu, Lin (Journal of Social Science and Humanities, 2025)
City slogans play a vital role in facilitating communication between cities and highlighting their unique charm. High-quality slogans are essential for boosting economic development, reviving historical and cultural heritage, and projecting positive images of cities. This survey has compiled slogans from 38 cities in Hubei Province as its corpus and analyzes them from various angles, including content elements, linguistic characteristics, prevalent issues, and quality enhancement, with the aim of offering fresh insights into the promotion of city images.